DHA-rich fish oil and Tualang honey reduce chronic stress-induced oxidative damage in the brain of rat model - Asari, Mohd Asnizam; Kuttulebbai Naina Mohamed Salam, Sirajudeen; Mohd Yusof, Nurul Aiman; Mohd Amin, Mohamad Syabil Ikhwan (Center for Food and Biomolecules, National Taiwan University, 2022)
Background: Exposure to chronic stress induces oxidative damage which alters the dynamic balance between antioxidant and pro-oxidant activities in the brain. Tualang honey (TH) is a Malaysian wild multifloral honey which has been shown to contain high amount antioxidants. DHA-rich fish oil is a form of omega-3 fatty acids found in fish which also possesses some antioxidant activity. This study aimed to evaluate anti-stress activity of DHA-rich fish oil, TH and their combination on several parameters of oxidative stress in chronic stress rat model. Methods: Fifty male Sprague Dawley rats were divided into (i) control, (ii) stress-exposed, (iii) stressexposed and treated with TH (1 g/kg body weight twice daily), (iv) stress-exposed and treated with DHA-rich fish oil (450 mg/kg body weight twice daily), and (v) stress-exposed and treated with a combination of TH and DHA-rich fish oil. The chronic stress regimen consisted of a combination of restraint stress and a swim stress test for 28 days. Results: DHA-rich fish oil and TH significantly (p < 0.05) supressed stress-induced elevation of serum corticosterone and lipid peroxidation, and caused a significant increase in total antioxidant capacity. For glutathione status, only TH significantly reduced stress-induced elevation of oxidised glutathione (GSSG) and normalised GSH/GSSG ratio. Conclusion: Both DHA-rich fish oil and TH have protective effects against brain oxidative stress but consuming these substances together does not seem to provide an additional benefit compared to consuming them separately.